Acrodermatitis enteropathica during parenteral nutrition: a pediatric case report - Proli, Francesco; Margiotta, Gaia; Ferretti, Serena; Drosi, Alessandra; Valentini, Piero; Buonsenso, Danilo; Onesimo, Roberta; Giorgio, Valentina; Guerriero, Cristina; Zampino, Giuseppe; Lazzareschi, Ilaria (Acta Biomedica Atenei Parmensis, 2023)
Background and aim Acrodermatitis enteropathica is a rare disorder characterized by the triad composed by dermatitis, alopecia and diarrhoea. Its acquired form can be caused by inadequate zinc intake, malabsorptive processes, excessive renal or intestinal loss. A rare cause of acquired zinc deficiency is iatrogenic nutritional deficiency due to parenteral nutrition. The diagnosis can be really difficult because the early clinical signs are non-specific and patient’s eventual comorbidities can often mask symptoms. Methods: A 5-years-old child affected by several comorbidities, consequent to C. Koseri meningo-encephalitis occurred in the neonatal period, was admitted to Pediatric ward for acute pancreatitis and had been fed via total parenteral nutrition for one month. Symptoms started approximately 15 days after the start of a standardized parenteral nutrition mixture. The child presented with diarrhoea, alopecia and erythematous bullous skin lesions, distributed predominantly in acral and periorificial sites and not responsive to topical treatments. Zinc serum dosage were very low (10 µg/dL, with normal values 68-107 µg/dL). Clinical improvement was very fast after oral zinc supplementation (5mg/daily), with a rapid regularisation in the intestinal habits and re‐epithelialization of the skin lesions. Results and Conclusions: Trace elements are an essential component of parenteral nutrition. The supplementation of trace elements is an important part of the parenteral nutrition prescription. Even few days of zinc shortage, especially in frail patients, may cause a severe dermatitis that can be easily prevented. Despite its rarity, acrodermatitis enteropathica should be strongly considered in the differential diagnosis of skin lesions for these patients.